India's grand strategy history, theory, cases - Bajpai, Kanti P. 1955- (War and international politics in South Asia, 2014)
As India prepares to take its place in shaping the course of an 'Asian century', there are increasing debates about its 'grand strategy' and its role in a future world order. This timely and topical book presents a range of historical and contemporary interpretations and case studies on the theme. Drawing upon rich and diverse narratives that have informed India's strategic discourse, security and foreign policy, it charts a new agenda for strategic thinking on postcolonial India from a non-Western perspective. Comprehensive and insightful, the work will prove indispensable to those in defence and strategic studies, foreign policy, political science, and modern Indian history. It will also interest policy-makers, think-tanks and diplomats.